Microbubble destruction during intravenous administration: a preliminary study. - Barrack, T; Stride, E (2009)
The concentration and size distribution of microbubble suspensions are important parameters for both diagnostic and therapeutic applications. The aim of this preliminary study was to investigate the relationship between changes in the microbubble population and the administration process variables, specifically syringe inner diameter, needle inner diameter, volume flow rate and the liquid in which the microbubbles are suspended. It was found that reducing either the syringe or needle inner diameter produced large reductions in microbubble concentration during administration, as much as 99.9% for needle inner diameters <0.24 mm. Increasing the volume flow rate up to 3 mL/min and changing the suspending fluid from distilled water to glycerol, however, were both found to reduce the degree of microbubble destruction. Further work is needed to fully explain these observations. However, investigation of the response of microbubbles to changes in hydrostatic pressure only, indicated that this was unlikely to be the main mechanism of destruction and hence that shear stress was a more important factor. Comparison with findings from another recent study of microbubble stability indicated that microbubble size, concentration and composition were also important parameters and should be taken into account in designing administration procedures for microbubble agents. It was concluded that current procedures should be reviewed, particularly for therapeutic applications, and that the results should also be taken into account when assessing the accuracy of microbubble size distribution measurements obtained using automatic particle sizing equipment in which microbubbles are made to flow under pressure.